Peningkatan Loyalitas Pelanggan Melalui Integrasi Digital Marketing dan Desain Kemasan Produk Berbasis Behavioral Consumer Insights Pada UMKM - Ifriza, Yahya Nur; Efrilianda, Devi Ajeng; Mandaya, Yusuf Wisnu; Alamsyah, Alamsyah (Jurnal Abdi Negeri, 2024)
Customer loyalty is an important element that determines the long-term success of MSMEs, especially in the midst of increasingly fierce market competition. Previous research shows that digital marketing and attractive packaging design play an important role in increasing customer loyalty and attracting new consumers emphasize that digital-based marketing strategies enable small and medium businesses to reach a wider market at low costs, while research by [3] shows that consumer behavior-based packaging design can increase consumer appeal and trust. Based on these results, this service program aims to integrate digital marketing strategies and packaging design based on behavioral consumer insights in 15 MSMEs in the culinary and crafts sectors. The results of the service showed an increase in MSMEs' understanding of digital marketing from 30% to 85% after the training. In addition, assistance with packaging design resulted in an increase in product attractiveness from 25% to 78%. Customer loyalty also increased significantly, with 68% of customers making repeat purchases after implementing the new strategy. This program supports previous research which confirms that the integration of digital marketing strategies and packaging design based on consumer behavior can increase MSME customer loyalty and competitiveness in the market.